Sexuality after 60 years of age (2010)
The noticeable increase in the portion of the population that is over 60 years of age leads us to think in those aspects that have incidence in the quality of life of those adults and not just on morbidity and mortality figures. Sexuality of senior adults, as a quality of life indicator, requires greater understanding of those factors that have impact, over and beyond those changes in morphology and physiology. This article invites one to think of those factors and to contribute in eliminating myths regarding sexuality of humans in general and of senior adults in particular.